The effect of educational intervention program on promoting preventive behaviors of urinary tract infection in girls: a randomized controlled trial - Zahra Ahmadi; Mohsen Shamsi; Nasrin Roozbahani; Rahmatollah Moradzadeh (BMC, 2020)
Abstract Background Urinary tract infection is one of the most common infectious diseases in children, which can lead to serious complications for a child. The purpose of this study was to investigate the impact of Theory Planned Behavior (TPB) -based education on the promotion of preventive behaviors of urinary tract infection in mothers with a daughter under age two. Methods The present study is an educational randomized controlled trial that its sample consisted of 100 mothers who had a daughter under age two. They were selected through convenience sampling and then were randomly assigned to the intervention and control groups (each group included 50 participants). The data collection tool was a reliable and valid questionnaire based on TPB constructs. First, in both groups, the pre-test was administrated and then the educational intervention in the intervention group was conducted in the form of four educational sessions in 1 month (based on the pre-test need assessment) and then 3 months after the intervention (according to the ideas of Panel of Experts), post-test in both groups was administrated and then the data were analyzed through SPSS version 23 software with inferential statistics (independent t-test, paired t-test, and chi-square). The significance level was considered 0.05. Results Three months after the intervention, the mean score of the constructs of TPB in the intervention group was significantly higher than the control group. The performance of prevention of urinary tract infection in the intervention group before the education increased from 2.85 ± 0.51 to 3.74 ± 0.29 (out of 4) (p = 0.001). Conclusions TPB-based education with active and interventional follow-up was effective in promoting the preventive behaviors of urinary tract infection. Therefore, due to the side effects of UTI, especially in vulnerable periods such as childhood, it is recommended that trainings based on this model be carried out in other health care centers in order to maintain children health. Trial registration This trial has been registered at IRCT, IRCT2017031533090N1. Registered on 9 July 2017, https://en.irct.ir/trial/25621